Penyuluhan dan Pelatihan Kegawatdarutan Medis dan Pertolongan Pertama pada Gigi Lepas pada Para Kader PKK - Eddy; Tjandrawinata, Rosalina; Liliany Margareta, Dewi; Tri Oka Binartha, Cipthadi; Widhiyaningsih, Dhyani; Halim, Himawan (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2025)
Community service is one of the three pillars of higher education that must be implemented by every higher education institution, including the Faculty of Dentistry. This activity aims to apply knowledge and skills in the field of dentistry to improve public health, especially in the promotive and preventive aspects. The Faculty of Dentistry, Trisakti University, carried out community service activities in the form of counseling and training on medical emergencies and first aid for loose teeth in collaboration with the Family Welfare Movement (PKK) Cadres of Grogol Village, West Jakarta, focused on two main topics, namely the Heimlich technique and initial treatment for loose teeth. The activity was carried out on Thursday, May 15, at the Grogol Village Office located at Jl. Dr. Nurdin Raya No. 41–43, RT.9/RW.8, Grogol Village, Grogol Petamburan District, West Jakarta. 24 participants participated in the counseling by taking a pre-test before the counseling and a post-test after the counseling. The post-test results showed a significant increase in knowledge.